The role of local impedance drop in the acute lesion efficacy during pulmonary vein isolation performed with a new contact force sensing catheter. (19th May 2022) - Szegedi, N; Perge, P; Sallo, Z; Piros, K; Nagy, VK; Osztheimer, I; Merkely, B; Geller, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary vein isolation (PVI) is the cornerstone treatment for paroxysmal atrial fibrillation (AF). The effective lesion creation during the PVI is essential to reach optimal long-term results. Purpose: Our pilot study aimed to evaluate the role of local impedance drop in lesion formation during pulmonary vein isolation with a novel contact force sensing ablation catheter that records local impedance as well and to find a local impedance cut-off value that predicts successful lesion formation. Materials and methods: After completing point-by-point radiofrequency pulmonary vein isolation, the success of the applications was evaluated by pacing along the ablation line at 10 mA, 2 ms pulse width. Lesions were considered successful if loss of local capture was achieved. Results: Out of 645 applications, 561 were successful and 84 were unsuccessful. Compared to the unsuccessful ablation points, the successful applications were shorter (p=0.0429) and had a larger local impedance drop (p<0.0001). There was no difference between successful and unsuccessful applications in terms of mean contact force (p=0.8571), force-time integral (p=0.0699) and contact force range (p=0.0519). The optimal cut-point for the local impedance drop indicating successful lesion formation was 21.80 Ohms on the anterior wall [AUC=0.80 (0.75-0.86), p<0.0001], and 18.30 Ohms on the posterior wall [AUC=0.77 (0.72-0.83), p<0.0001]. A local impedance drop larger than 21.80 Ohms on the anterior wall and 18.30 Ohms on the posterior wall was associated with an increased probability of effective lesion creation [OR=11.21, 95%CI 4.22–29.81, p<0.0001; and OR=7.91, 95%CI 3.77–16.57, p<0.0001, respectively]. Conclusion: The measurement of the local impedance may predict optimal lesion formation. A local impedance drop > 21.80 Ohms on the anterior wall and > 18.30 Ohms on the posterior wall significantly increases the probability of creating a successful lesion.